2019
DOI: 10.3168/jds.2018-15616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extended colostrum feeding on plasma glucagon-like peptide-1 concentration in newborn calves

Abstract: Glucagon-like peptide-1 (GLP-1) plays a role in the regulation of glucose homeostasis via the stimulation of insulin secretion. The objective of this study was to evaluate the effect of extended colostrum feeding on plasma concentration of GLP-1. Holstein bull calves (n = 27) were fed pooled colostrum at 7.5% of birth body weight at 2 h after birth and then fed mature milk (M), a 50:50 mixture of pooled colostrum and milk (CM), or pooled colostrum (C; n = 9 for each treatment) at 5% of birth body weight at 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
1
15
1
5
Order By: Relevance
“…Collectively, these results highlight several important notions. First, given that all calves within the current study rapidly surpassed FPT thresholds, we are confident that results within this study and companion studies (Inabu et al, 2019;Pyo et al, 2020) are not confounded by inadequate PT between treatments. Second, our data showed that serum IgG >20 g/L can be achieved early on, supporting the use of higher thresholds to determine adequate PT (Furman-Fratczak et al, 2011;Chigerwe et al, 2015).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Collectively, these results highlight several important notions. First, given that all calves within the current study rapidly surpassed FPT thresholds, we are confident that results within this study and companion studies (Inabu et al, 2019;Pyo et al, 2020) are not confounded by inadequate PT between treatments. Second, our data showed that serum IgG >20 g/L can be achieved early on, supporting the use of higher thresholds to determine adequate PT (Furman-Fratczak et al, 2011;Chigerwe et al, 2015).…”
Section: Discussionmentioning
confidence: 65%
“…In addition, the colostral bioactive fraction is critically important in promoting gastrointestinal tract development (Bühler et al, 1998;Blättler et al, 2001;Steinhoff-Wagner et al, 2014) and possibly modulating neonatal metabolism from the absorption of hormones such as insulin (Pierce et al, 1964;Kirovski et al, 2008), leptin, or adiponectin (Kesser et al, 2015;Liermann et al, 2020). Regarding TM or part-colostrum mixtures, preliminary data indicate that these do positively affect the metabolic and hormonal profiles of neonatal calves (Inabu et al, 2019;Pyo et al, 2020). It is also very clear that TM, colostrum-milk mixtures, or prolonged colostrum feedings promote gastrointestinal development (Yang et al, 2015;Pyo et al, 2020), although the degree of gastrointestinal development with TM or colostrum-milk mixture feeding appears to be equivalent to prolonged colostrum feeding only when an initial meal of colostrum is provided (Yang et al, 2015;Pyo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Taylor‐Edwards et al () reported that GLP‐2 effects were observed in ruminants in a manner similar to that of non‐ruminants. Our previous study indicated that the higher plasma concentration of glucagon‐like peptide‐1, which is co‐secreted with GLP‐2 from same cells, was associated with a greater intestinal villi length in newborn calves (Inabu et al, ). Based on these factors, it could be inferred that TB supplementation to MR might stimulate GIT development via the increased circulating GLP‐2 level, which can improve nutrient absorption in pre‐weaning calves.…”
Section: Resultsmentioning
confidence: 99%
“…The elevated glucose availability and the improved insulin status in colostrum-fed calves are important prerequisites for the accelerated maturation of the somatotropic axis, as indicated by several studies in neonatal calves that were previously summarised (Blum, 2006;Hammon et al, 2012). The stimulation of gastrointestinal hormones due to colostrum feeding may contribute to the elevated insulin secretion in the calves (Hadorn et al, 1997;Inabu et al, 2019). The elevated insulin status due to colostrum feeding in neonatal calves is probably the trigger for stimulating endogenous Developmental effects of milk feeding in calves IGF-I and the postnatal somatotropic axis (Hammon et al, 2012) because glucose and insulin stimulate the hepatic gene expression of the growth hormone receptor and IGF-I as well as IGF-I secretion (Brameld et al, 1999;Butler et al, 2003).…”
Section: Colostrum Supply and Maturation In The Somatotropic Axismentioning
confidence: 99%